Pengembangan Model Pembelajaran Terpadu untuk Pendidikan Islam Anak Usia Dini - Manora, Hecksa; Khasanah, Nevi Laila; Solimin, Solimin; Sari, Meilida Eka (Bouseik: Jurnal Pendidikan Islam Anak Usia Dini, 2024)
Early Childhood Islamic Religious Education (PIAUD) plays an important role in shaping the character and religious understanding of early childhood. However, ensuring the quality of Islamic education in the early stages of a child's development poses significant challenges. To overcome this problem, research was conducted to design and test a PIAUD integrated learning evaluation management model based on Islamic values. This research uses a qualitative research approach. The research methodology used is collaborative action research (CAR) with the CIPP (Context, Input, Process, Product) approach. This research collects data through various methods such as observation, interviews, and document analysis. The research results show that applying this evaluation model can significantly increase students' understanding of religious concepts and encourage character development. In addition, this research highlights the importance of collaboration between educational institutions, parents and the community to support the PIAUD learning evaluation process. Overall, this research provides valuable insights into improving the quality of Islamic education for children and underscores the important role of collaborative efforts in achieving this goal.